Solidarity and Humanism: The Red Cross Within the Socialist Framework of Yugoslavia in the 1960s and 1970s - Antonijević, Pavle (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2025)
The Red Cross has a rich history, having existed in both capitalist and state-socialist systems, providing a broad research scope. This paper focuses on the work of the Red Cross in Socialist Yugoslavia, aiming to explore how the organization was perceived within that system. It highlights the significance of the concept of self-management in shaping the organization’s mission. The paper further explores the key principles of socialist humanism and solidarity that were the basic conceptual framework guiding the activities of the Red Cross. It also examines how the dominant ideological and political narratives of Socialist Yugoslavia influenced the organization. The main conclusion is that the Red Cross in Socialist Yugoslavia expanded its purpose, aiming to go beyond the limitations of being merely a humanitarian and charitable organization as understood in a capitalist context.